PERANCANGAN SISTEM PINTU OTOMATIS PADA WAREHOUSE BERBASIS ARDUINO DENGAN MENGGUNAKAN SENSOR IR - Febrian Febrian; Andien Putri Aullia, Fariz Dinata Faridhi, Paduloh (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The research discusses the design of an automatic door system for warehouses based on Arduino microcontroller, utilizing infrared (IR) sensors. The aim of this study is to enhance operational efficiency in managing the flow of goods in and out of the warehouse. The system is designed to automatically open and close doors when detecting objects, reducing manual intervention and increasing security and access speed. The research methodology includes hardware experimentation and a prototyping approach, allowing for comprehensive testing and evaluation of the system. In the development phase, components such as IR sensors, servo motors, and Arduino microcontrollers are integrated to form an interconnected system. Test results indicate that the system operates effectively, accurately detects objects, and responds quickly. This automatic door not only boosts productivity but also helps maintain the environmental conditions of the warehouse, such as temperature and cleanliness. Therefore, this research significantly contributes to the application of automation technology in industry, particularly in warehouse management